Answer:
1) A
2) B
Explanation:
The formula of rate of change from a certain number to another is
f(b) - f(a)
-----------
b - a
(i tried making a fraction if u couldnt tell)
Now substitute the values of x into the equation
(3*(-1) + 2) - (3*(1) +2)
----------------------------
-1 - 1
now combine everything together:
(-3+2) - (3+2)
------------------
-2
-1 - 5 -6 3
------- = ------- = ----
-2 -2
now do the same for the second question
(0^2 + 3) - (3^2 + 3) (3 - 12) -9 3
-------------------------- = ---------- = ---------- = ----- (answer choice B)
0 - 3 -3 -3